Analisis Kemampuan Mahasiswa Dalam Mengidentifikasi Tumbuhan di Lingkungan STKIP Soe - Angreni Liunokas (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2020)
This study aims to determine the ability of students to identify plant species and to identify the types of plants identified. This type of research is quantitative descriptive with the subject of 29 students of Biology Education Study Program STKIP Soe in the 2018/2019 school year who took the course of Plant Anatomy and Morphology. The research began with the preparation of the instrument, taking students to explore plants in the campus environment and taking specimens identification, then providing identification test questions. Observations were made during student activities. Data processing of test results and observation sheets by counting the total score and converted into a value form then interpreting the value based on the predicate. Based on the results of research students ‘ability to identify plants based on indicators observing the characteristics of plant specimens achieved only students look capable but not maximal so categorized enough and the results of observations of students’ ability to identify plant species in the medium category. The results of identification there are 43 types of plants that are classified into 27 families.